Effects of spirituality and social responsibility on job satisfaction: a conceptual analysis from religious perspectives - Kamil, Naail Mohammed; Sulaiman, Mohamed; Osman-Gani, Aahad M.; Ahmad, Khaliq (2011)

(untitled)
Although the concept of spirituality in the workplace has received enormous attention from contemporary researchers, very little or not sufficient research has been attempted from the religious perspective. This conceptual paper attempts to enrich the understanding of the spirituality in the workplace phenomenon from an Islamic Management perspective. In doing so, the conceptual paper attempts to study the theoretical and practical meanings of Taqwa, the characteristics of Taqwa, the two dimensions of Taqwa known as the Islamic spirituality and Islamic social responsibility, together with the mediating effect of “sabr” i.e. patience.